Safety and efficacy of digital single-operator pancreatoscopy for obstructing pancreatic ductal stones - Brewer Gutierrez, Olaya I.; Raijman, Isaac; Shah, Raj J.; Elmunzer, B. Joseph; Webster, George J.M.; Pleskow, Douglas; Sherman, Stuart; Sturgess, Richard P.; Sejpal, Divyesh V.; Ko, Christopher; Maurano, Attilio; Adler, Douglas G.; Mullady, Daniel K.; Strand, Daniel S.; DiMaio, Christopher J.; Piraka, Cyrus; Sharahia, Reem; Dbouk, Mohamad H.; Han, Samuel; Spiceland, Clayton M.; Bekkali, Noor L.H.; Gabr, Moamen; Bick, Benjamin; Dwyer, Laura K.; Han, Dennis; Buxbaum, James; Zulli, Claudio; Cosgrove, Natalie; Wang, Andrew Y.; Carr-Locke, David; Kerdsirichairat, Tossapol; Aridi, Hanaa Dakour; Moran, Robert; Shah, Shawn; Yang, Juliana; Sanaei, Omid; Parsa, Nasim; Kumbhari, Vivek; Singh, Vikesh K.; Khashab, Mouen A. (Endoscopy International Open, 2019)
Background and study aims The role of the digital single-operator pancreatoscopy (D-SOP) with electrohydraulic (EHL) or laser lithotripsy (LL) in treating pancreatic ductal stones is unclear. We investigated the safety and efficacy of D-SOP with EHL or LL in patients with obstructing pancreatic duct stones.Patients and methods Retrospective analysis of 109 patients who underwent D-SOP for pancreatic stones at 17 tertiary centers in the United States and Europe from February 2015 to September 2017. Logistic regression was performed to identify factors associated with the need for more than one D-SOP with EHL/LL.Results Most patients were males (70.6 %),mean age 54.7 years. Fifty-nine (54.1 %) underwent EHL and 50 (45.9 %) underwent LL. Mean procedure time was longer in the EHL group (74.4 min vs 53.8 min; P < 0.001). Ducts were completely cleared (technical success) in 89.9 % of patients (94.1 % in EHL vs 100 % in LL; P = 0.243), achieved in a single session in 73.5 % of patients (77.1 % by EHL and 70 % by LL; P= 0.5).D-SOP failed in 11 patients (10.1 %); 6 patients were treated with extracorporeal shockwave lithotripsy (ESWL), 1 with surgery,1 with combined treatment (ESWL + D-SOP EHL) and 3 with other. Fourteen adverse events occurred in 11 patients (10.1 %). Patients with more than three ductal stones were more likely to have technical failure compared to those with less than three stones (17 % vs. 4.8 %; P = 0.04). Having more than three stones was independently associated with the need for more than one D-SOC EHL/LL session (OR 2.94, 95 % CI 1.13 – 7.65).Conclusion D-SOP with EHL or LL is effective and safe in patients with pancreatic ductal stones.